The number of war-related traumatic events is associated with increased behavioural but not emotional problems among Syrian refugee children years after resettlement - (:unkn) unknown (UNIV SAO PAULO, INST PSIQUIATRIA, 2018)
Background: Turkey is the leading refugee-hosting country in the world. However, there are few studies which investigate mental wellbeing of refugee children in Turkey. Objective: The paper aims to examine the prevalence of emotional and behavioural problems and associated risk factors among Syrian refugee minors in Turkey. Methods: The research involved 85 students from 2th to 8th grades. We investigated emotional and behavioural problems with parent-reported Arabic form of Strength and Difficulties Questionnaire (SDQ). Socio-demographical findings and children's war-related experiences were also examined. Results: The study sample consisted of 49 (63.6%) girls, and 28 (36.4%) boys (total 77) from age 7 to 17. Average time after resettlement was 29.8 +/- 11.2 (5 to 50 months) months. 66 (85.7%) children reported to had lost at least one familiar person due to the war. The mean experienced war-related traumatic events were calculated as 2.92 +/- 1.86. Total difficulty scores of 30 (39.0%) children were above the cut off values. The rates of children whose SDQ problem scores exceeded the cut-off values were as high as 45.5% (35) for Emotional problems, 64.9% (50) for Peer, 27.3% (21) for conduct and 19.5% (15) for Hyperactivity problems. Discussion: Results indicate high prevalence rates of severe traumatic experiences and possible psychiatric disorders among child survivors of Syrian war which in its seventh year now.
Keywords: Syria; children; war; mental health; depression; SDQ; emotional problems; PTSD; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH; DIFFICULTIES QUESTIONNAIRE; RWANDAN CHILDREN; RISK-FACTORS; GAZA-STRIP; ADOLESCENTS; STRENGTHS; PTSD; DEPRESSION